Strategic Disclosure of Multiple Benchmarks in Earnings Announcements: An Examination of Investor Behavior Based on Internal and External Factors in the Performance Evaluation - Sri WAHYUNI; Jogiyanto Hartono (The Indonesian Journal of Accounting Research, 2013)
The objective of this study is twofold: (1) to provide empirical support regarding the effectiveness of strategic disclosure of multiple benchmarks in earnings announcements and (2) to explain the cognitive mechanism in processing the information with consequences that can affect the judgments of investors in evaluating company's performance. Prior research have described strategic disclosure of prior-period benchmark in earnings announcement that focus on the transitory gain or loss, which, in turn, influences investor's judgments (Schrand and Walther, 2000; Krische 2005). Using multiple reference-point theory from psychology, this study extendsprior research by investigating how investors behave differently to remainder effect and sufficient information available on external factors in earnings announcement. In addition, this study also investigates whether investors revise their evaluation when they are allowed to re-examine prior-period announcement. The experiment's results suggest that strategic disclosure of multiple benchmarks influences investor's judgments in evaluating company performance.